(untitled) (Research, Society and Development, 2023)
Objective: The differentiation between ischemic stroke and hemorrhagic stroke is essential to establish a course of treatment and an adequate prognosis. The present article aims to elucidate and compare different data on the use of computed tomography of the skull in the diagnosis of a stroke. Methodology: In the present study, a qualitative research was carried out, with the elaboration of a narrative review, using scientific articles available online on the Pubmed and Scielo platforms, as well as books referenced on the subject and also on online image databases, gathering and comparing the different data found in the sources that were consulted and listing the main topics on the use of computed tomography in the diagnosis of a stroke, whether ischemic or hemorrhagic. Results and discussion: Computed tomography of the skull is an imaging test that greatly aids in the diagnosis and clinical management of strokes. In the present study, computed tomography images of the skull were compared mainly for differentiation between ischemic stroke and hemorrhagic stroke. Conclusion: Computed tomography of the skull is the first-choice test in cases of suspected stroke, due to its excellent cost-benefit ratio and the speed at which the test can be performed in an emergency situation. The use of contrasts can assist in diagnoses, differential diagnoses elimination, and disease course time, whether early or late.